Otimização de parâmetros de pré-processamento para obtenção de feijão seco com reduzido tempo de cozimento. - Schoeninger, Vanderleia (2012)
The bean (Phaseolus vulgaris L) is a typical leguminous in Brazil. Its consumption should be encouraged due to the benefits of its quantity of protein, fiber, folic acid and minerals such as iron and potassium. However, its long cooking process consequently makes many consumers often avoid eating this product, which results in a decrease of production and demand. The possibility of offering a product previously processed, as well as keeping its technological characteristics with a short time of preparation, is an option for consumers who look for convenience and quality. Techniques as soaking and bleaching beans are presented as options for grains preprocessing. Thus, this study aim was investigating the effects of grains preprocessing with blanching and soaking applied under salt solutions according to the carioca bean quality parameters in order to obtain a dry product with a short cooking time. The maintenance of technological quality characteristics of in natura grain through the use of experimental design techniques was also considered. A Plackett and Burman experimental design was applied to evaluate the effects of nine factors in preprocessing: soaking time, soaking in sodium chloride concentration, soaking in sodium bicarbonate concentration, soaking temperature, blanching temperature, blanching time, concentration of sodium chloride under soaking, concentration of sodium bicarbonate under soaking and drying temperature based on responses as cooking time, splitting percentage and color difference (Δe*) of preprocessed grains related to control. In the optimization, a DCCR 23 plan was used only with factors of the maceration step which mainly contributed to reduce cooking time. The increased concentration of sodium bicarbonate used in the soaking of beans significantly reduced the cooking time, but it increased the damage level in the product and darkened the bean integument. This contributed to greater differences in color of preprocessed grains when compared to the control treatment. The factors that most influenced the studied answers were soaking time, concentration of sodium bicarbonate under soaking and drying temperature. The desirability technique allowed the answers simultaneous evaluation and the definition of optimal conditions for this process. This process presented overall desirability of 56.53%, thus the factors levels were defined according to the following conditions: soaking time of 13.1 hours, concentration of NaHCO3 under soaking solution of 2.3% and drying temperature of 50 °C. Under these conditions, it is possible to reduce the cooking time by 58% with an index of damaged grains near 9.13% and color difference of 8.39. The obtained results may contribute to future researches that aim at developing bean preprocessing quality in a shorter cooking time.